Queer love and urban intimacies in Martial Law Manila - Diaz, Robert G. (2012)
This article examines certain representations of Metropolitan Manila and the city's queer intimacies during Martial Law. In particular, it analyzes Ishmael Bernal's film Manila By Night (1980) and Jessica Hagedorn's novel Dogeaters (1990).
Released during a time when the Marcoses secured rule through an over-production of their "love team," and by IMF supported justifications for molding a "beautiful and efficient" Manila, Manila By Night challenges disciplinary plans for the city and its populace through the presence of queer characters that unabashedly love the dirty, dysfunctional and impoverished city. In a similar vein, Dogeaters incorporates characters that practice queer love as they navigate a version of Manila antithetical to the one the government and the neo-colonial elite produced for the West. Although coming from different genres, it is perhaps unsurprising that both Manila by Night and Dogeaters center on Manila as the quintessential space for queer revolutionary politics. Bernal and Hagedorn re-imagine Manila as connecting militant forms of queerness across geo-political spaces and temporalities. Both works also highlight the utility of a queer diasporic framework to understanding revolutionary politics during dictatorial rule.
Keywords: Manila City -- In literature; Manila City -- In motion pictures